Ghost-haunted land : Contemporary art and post-Troubles Northern Ireland - Long, Declan (Book collections on Project MUSE., 2017)
Since the signing of the Good Friday Agreement in 1998 - the formal end-point of the thirty-year modern 'Troubles' - contemporary visual artists have offered diverse responses to post-conflict circumstances in Northern Ireland. In Ghost-Haunted Land - the first book-length examination of post-Troubles contemporary art - Declan Long highlights artists who have reflected on the ongoing anxieties of aftermath. This wide-ranging study addresses developments in video, photography, painting, sculpture, performance and more, offering detailed analyses of key works by artists based in Ireland and beyond - including 2014 Turner Prize winner Duncan Campbell and internationally acclaimed filmmaker and photographer Willie Doherty. 'Post-Troubles' contemporary art is discussed in the context of both local transformations and global operations - and many of the main points of reference in the book come from broader debates about the place and purpose of contemporary art in today's world.